A Bayesian nonparametric model for Taguchi's on-line quality monitoring procedure for attributes - Tsunemi, Miriam Harumi [UNESP]; Campos, Thiago Feitosa; Esteves, Luís Gustavo; Leite, José Galvão; Wechsler, Sergio (Elsevier, 2012)
A Bayesian nonparametric model for Taguchi's on-line quality monitoring procedure for attributes is introduced. The proposed model may accommodate the original single shift setting to the more realistic situation of gradual quality deterioration and allows the incorporation of an expert's opinion on the production process. Based on the number of inspections to be carried out until a defective item is found, the Bayesian operation for the distribution function that represents the increasing sequence of defective fractions during a cycle considering a mixture of Dirichlet processes as prior distribution is performed. Bayes estimates for relevant quantities are also obtained. © 2012 Elsevier B.V.
Keywords: Bayesian estimation; Bayesian operation; Continued quality deterioration; Mixture of Dirichlet processes; Taguchi's procedure for attributes